2003
DOI: 10.1155/s1173912603000142
|View full text |Cite
|
Sign up to set email alerts
|

A two-stage heat transfer model for the peripheral layers of a grain store

Abstract: Abstract. An understanding of the flow of heat in grain store structures, in particular, within the peripheral layer, is important from many industrial perspectives. To analyse the heat transfer within such regions a mathematical model known as the two-stage heat transfer model is proposed. This model makes a distinction between the air and grain within the grain bulk, and thus takes into consideration the fact that the rate of heat transfer through the grain is different to that through the interstitial air s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Antic and Hill (2000) [2] are studied a mathematical model for heat transfer in grain store microclimates, this model is "double diffusivity" such that they are used the heat-balance integral method to transform the coupled partial differential equations to the coupled ordinary differential equations and solved it numerically by using the Fehlberg fourth-fifth order Rangekutta method. Antic and Hill (2003) [3] are studied a Two-stage heat transfer model for the peripheral layers of a grain store, they are observed that the predictions of the air and grain temperatures of the two-stage model lag behind those of the double-diffusivity heat transfer model, but this lag decreases as time increases.…”
mentioning
confidence: 99%
“…Antic and Hill (2000) [2] are studied a mathematical model for heat transfer in grain store microclimates, this model is "double diffusivity" such that they are used the heat-balance integral method to transform the coupled partial differential equations to the coupled ordinary differential equations and solved it numerically by using the Fehlberg fourth-fifth order Rangekutta method. Antic and Hill (2003) [3] are studied a Two-stage heat transfer model for the peripheral layers of a grain store, they are observed that the predictions of the air and grain temperatures of the two-stage model lag behind those of the double-diffusivity heat transfer model, but this lag decreases as time increases.…”
mentioning
confidence: 99%